DNA methylation array analyses identified breast cancer‐associated HYAL2 methylation in peripheral blood. Issue 8 (24th September 2014) - Yang, Rongxi; Pfütze, Katrin; Zucknick, Manuela; Sutter, Christian; Wappenschmidt, Barbara; Marme, Frederik; Qu, Bin; Cuk, Katarina; Engel, Christoph; Schott, Sarah; Schneeweiss, Andreas; Brenner, Hermann; et al.
<x xml:space="preserve">Abstract</x> Breast cancer (BC) is the leading cause of cancer‐related mortality in women worldwide. Changes in DNA methylation in peripheral blood could be associated with malignancy at early stage. However, the BC‐associated DNA methylation signatures in peripheral blood were largely unknown. Here, we performed a genome‐wide methylation screening and identified a BC‐associated differentially methylated CpG site cg27091787 in the hyaluronoglucosaminidase 2 gene (HYAL2) (discovery round with 72 BC case and 24 controls: p = 2.61 × 10−9 adjusted for cell‐type proportions). The substantially decreased methylation of cg27091787 in BC cases was confirmed in two validation rounds (first validation round with 338 BC case and 507 controls: p < 0.0001; second validation round with 189 BC case and 189 controls: p < 0.0001). In addition to cg27091787, the decreased methylation of a 650‐bp CpG island shore of HYAL2 was also associated with increased risk of BC. Moreover, the expression and methylation of HYAL2 were inversely correlated with a p‐value of 0.006. To note, the BC‐associated decreased HYAL2 methylation was replicated in the T‐cell fraction (p = 0.034). The cg27091787 methylation level enabled a powerful discrimination of early‐stage BC cases (stages 0 and I) from healthy controls [area under curve (AUC) = 0.89], and was robust for the detection of BC in younger women as well (age < 50, AUC = 0.87). Our study reveals a strong association between decreased HYAL2 methylation in peripheral blood and BC, and provides a promising blood‐based marker for the detection of early BC.